Design of a Temporary Optical Coupler Using Fiber Bending for Traffic Monitoring - Takui Uematsu; Hidenobu Hirota; Tomohiro Kawano; Takanori Kiyokura; Tetsuya Manabe (IEEE Photonics Journal)
We design a temporary optical coupler that extracts 1.25-Gbps optical signals for traffic monitoring. The temporary optical coupler employs a fiber bending technique that uses a receiving fiber to receive leaked signal light from a bent fiber. We optimize the bending condition and the receiving fiber to obtain a high extraction efficiency while keeping the bending loss below 2 dB. We also measure the bit error rates for the 1.25-Gbps signals and reveal that our temporary optical coupler extracts the 1.25-Gbps optical signals without any deterioration in signal quality. Finally, we confirm experimentally that we achieved traffic monitoring using a traffic monitoring system and our temporary optical coupler in a fiber-to-the-home access network system based on a gigabit Ethernet passive optical network.